Techniques of Teaching Library Science - Kaula, P. N. (Journal of Information and Knowledge, 2002)
Ascribes the present deterioration in the teaching of library science in India partly to the sudden increase in the number of universities giving post-graduate courses. Points out that the fall in the standard of professional education of librarians in India is largely due to ineffective methods of teaching and not to the curriculum recommended by the University Grants Commission. Describes Ranganathan’s methods of classroom coaching being largely discussional punctuated by a few effective lectures and supplemented by tutorial work, and weekly colloquia, his integrating theory and practice, and his intimate contact with each individual student to initiate him into systematic thinking and research methods. Suggests a prior field experience of three years and also a systematic training in the art of teaching, for teachers of library science.